From private entrepreneurship to state monopoly: contracting Swiss soldiers for Dutch Service under Ancien Régime Fiscal- Military Practices (1693–1829) - Depreter, M (Brill Publishers, 2024)
This contribution examines Dutch contracting practices to hire Swiss troops during the Ancien Régime, from the first contracts directly negotiated in the Protestant cantons by Petrus Valckenier (1693-1694) during the Nine Years’ War, seizing opportunities arisen from Louis XIV’s revocation of the Edict of Nantes (1685) after a period during which the Dutch seem to have relied on uncertain access to Swiss manpower through French intercession, up to the end of a short-lived revival of Swiss foreign regiments in the newly-instated Kingdom of the Netherlands (1814-1829). Evolving contracting practices reveal increasing interference by both the Swiss cantonal authorities, desiring to retain control over this manpower and to ensure favourable terms of service to troops led by their socio-political elites, and by the Dutch polity (United Provinces, then Kingdom of the Netherlands), desiring to increase discipline and efficiency at the lowest cost. During this process, which eventually saw the emergence of national armies and the dismissal of foreign troops in Dutch service, military entrepreneurs slowly lost out as territorial political authorities managed to enforce their sovereignty more strictly. Such a change is reflected both in the negotiation process (actors and places of negotiation) and in the content of the concluded capitulations.